Representasi Perempuan dalam Film Indonesia - Andriani, Reni (Harakat an-Nisa: Jurnal Studi Gender dan Anak, 2024)
This study aims to analyze the representation of women in Indonesian films through a literature study method, by combining primary and secondary data. Analysis was carried out on the characterization, dialogue, and visual narrative in various films to identify patterns of gender representation. The findings of the study show that despite some efforts to feature women in stronger and multidimensional roles, traditional gender stereotypes are still dominant. The implications of these findings emphasize the importance of awareness and change in the film industry to create more balanced and realistic representations, which can influence people's views of gender roles. The study also identified limitations in the number of samples and genres of films analyzed, and suggested that future research expand the scope and consider other factors such as the influence of social media and technological changes in film production and consumption.